Efficacy and Adverse Event Profile in Patients Receiving “Shorter Oral Bedaquiline-containing Multidrug-resistant/Rifampicin-resistant Tuberculosis Regimen” in a Tertiary Care Hospital in Eastern India - Hindol Mondal; Manasi Basu Banerjee; Abheek Das; Somnath Maity (Journal of Advanced Lung Health)
Introduction: Multidrug resistant/rifampicin-resistant tuberculosis (MDR/RR-TB) is a leading cause of death in India. To combat this, National TB Elimination Programme, erstwhile RNTCP) has launched “shorter oral bedaquiline (Bdq)-containing MDR/RR-TB regimen” from March 2021 replacing the injectable containing MDR/RR-TB regimen in a phased manner. Objective: We want to measure the outcome and safety profile of this newly introduced shorter oral Bdq-containing MDR/RR-TB regimen.” Materials and Methods: A prospective observational study was conducted to evaluate the effectiveness and adverse drug reaction (ADR) profile of “Shorter oral Bdq-containing regimen.” After getting approval from the ethics committee, all MDR/RR-TB subjects receiving the regimen from MDR-TB clinic of Malda Medical College were included in the study and followed up. Sociodemographic data and treatment outcome details were evaluated. ADRs were evaluated for causality, severity assessment, and management aspects. Result: Of the total, 96 patients were assessed for eligibility. Sixty-three patients were enrolled (n = 63), followed up and analyzed. 19 (30%) patients were cured while 33 (52.4%) patients more had completed treatment. 6 (9.5%) patients declared as treatment failure. One subject died during treatment. Four patients were lost to follow-up (6.4%). In total, 189 ADRs were reported. Commonly observed ADRs were anorexia (60%), nausea (51%), and weakness (46%). Majority were “possible” category by causality assessment and “mild” in severity assessment. Hepatitis was only severe ADR observed. Conclusion: Success rate and adherence observed with this regimen were encouraging. ADRs were mostly mild and managed symptomatically with regular monitoring in some cases.